Role of delayed salvage bevacizumab at symptomatic progression of chemorefractory glioblastoma - Moire Cuncannon; Matthew Wong; Dasantha Jayamanne; Linxin Guo; Nicola Cove; Helen Wheeler; Michael Back (BMC Cancer, 2019)
Abstract Background Assess benefit of salvage bevacizumab (BEV) at time of symptomatic progression in patients with refractory glioblastoma (GBM). Methods Patients managed with adjuvant long course chemo-radiation therapy for GBM were entered into a prospective database. At chemorefractory symptomatic progression, patients were offered BEV or best supportive care. Re-irradiation (ReRT) was used with BEV in selected patients. BEV continued indefinitely until deterioration limited hospital based infusion. The primary endpoint was median survival calculated from date of decision for BEV to proceed (BEVstart), or decision to decline BEV (BEVreject). Results Fifty-five patients were managed of which 48 patients have relapsed disease. The median survival post relapse was 6 months (95%CI: 4.6–7.4). At relapse, 28 patients received BEV with only 14% delivered at first relapse. The median number of BEV cycles was 8 (range 1–25). ReRT was subsequently used in 16 (33%) relapsed patients. BEV treated patients were associated with improved median survival post relapse with 9 months vs 3 months (p < 0.01). The median survival from BEV related decision-making at symptomatic refractory progression to death was 4 months (95%CI: 2.0–6.0). BEVstart was associated with improved survival from this date with median survival of 6 months vs 1 month with BEVreject (p < 0.01). Median survival with ReRT from this date was 8 months vs 3 months without ReRT (p = 0.01). In the BEV patients at eventual progression, death occurred at a median of 30 days post BEV cessation. Conclusion In this clinic managing selected patients with chemorefractory progressive glioblastoma, delayed salvage bevacizumab, often in combination with re-irradiation, may provide an increase in survival duration compared with best supportive care.